Self-Assembled Human IgG Monolayers on Mixed Thiols Modified Gold Surfaces - Lv, Zhengjian; Wang, Jianhua; Chen, Guoping (Asian Journal of Chemistry, 2013)
The human IgG protein monolayers were fabricated on mixed thiols modified gold substrates by self-assembled monolayers method. The surface properties of protein monolayers were characterized by contact angle measurements, X-ray photoelectron spectroscopy and atomic force microscopy, respectively. It was found that the contact angles of the protein layers on the mixed thiols films containing 20 %, 40 %, 60 %, 80 %, 100 % of 16-mercaptohexadecanoic acid were 83.5 ± 3.3º, 56.7 ± 3.1º, 38.6 ± 2.9º, 25.8 ± 2.6º, 14.2 ± 2.3º, respectively. The atomic concentration of nitrogen of protein layers on pure 16-mercaptohexadecanoic acid film was counted to be 11.43 ± 0.56 %. Depth profile analysis showed the protein layer and 16-mercaptohexadecanoic acid film have the thickness of 7 nm and 2 nm, respectively. Furthermore, the adhesive forces between antibody and antigen layers with molar ratios of 16-mercaptohexadecanoic acid of 0, 0.2, 0.4, 0.6, 0.8 and 1.0 were determined to be 11 ± 2, 158 ± 21, 325 ± 24, 589 ± 36, 814 ± 41, 883 ± 45 pN, respectively. In summary, these results suggested that the human IgG protein monolayers were successfully formed and the surface coverage of protein molecules increased parallel with the increasing of 16-mercaptohexadecanoic acid content. Thus, they demonstrated that the mixed thiols based self-assembled monolayers method is a reliable technique for fabricating protein monolayers with adjustable surface coverage and good controllability.